Cytoplasmic droplet acting as a mitochondrial modulator during sperm maturation in dogs - Angrimani, D. S.R. (2017)
Motility acquisition during sperm maturation and passage through the epididymis is closely related to mitochondrial function and appears to occur in parallel with cytoplasmic droplet (CD) migration. However, such mechanism remains unclear in dogs. Thus, the aim of this study was to characterize the influence of sperm CD in the mitochondrial functionality during epididymal sperm maturation in dogs. Twenty-one adult dogs were submitted to elective bilateral orchiectomy. Testicles were stored for 18–24 h at 5 °C and epididymal sperm samples were then collected from different segments of the epididymis (caput, corpus and cauda). Samples were evaluated for computer-assisted motility analysis (CASA), presence of CD (eosin/nigrosin stain), ultrastructural CD analysis and sperm mitochondrial activity (3,3' diaminobenzidine technique) and membrane potential (JC-1 probe). Samples collected from the corpus epididymis showed higher motility and mitochondrial activity in comparison to the caput sperm. Moreover, corpus sperm had lower percentage of proximal droplets compared to caput samples, while mitochondrial membrane potential remained unchanged. Cauda samples showed higher motility, mitochondrial activity and potential, however, lower presence of sperm droplets (proximal and distal). In conclusion, the CD is essential for epididymal sperm maturation in dogs, showing important functions along the transit in the epididymis. In the corpus segment, the migration of the CD along the sperm midpiece provides a high mitochondrial activity and the onset of sperm motility. On the other hand, sperm from cauda epididymis lack CD but suffered lipid membrane changes which allow a maximum mitochondrial membrane potential and motility.